Development of a targeted gene panel for the diagnosis of Gorlin syndrome. Issue 11 (November 2022) - Nakamura, Y.; Onodera, S.; Takano, M.; Katakura, A.; Nomura, T.; Azuma, T.
Abstract: Gorlin syndrome is a rare autosomal dominant disease caused by mutations in the PTCH1, PTCH2, and SUFU genes. Each symptom of the disease has a different time point of onset, which makes early diagnosis based solely on symptoms challenging. In this study, a gene panel was developed to overcome the challenges in the diagnosis of Gorlin syndrome and allow diagnosis using a single test. A custom panel was generated for four genes associated with Gorlin syndrome: PTCH1, PTCH2, SMO, and SUFU . Twenty-seven samples from 12 patients with Gorlin syndrome and three asymptomatic blood relatives of the patients were examined. This panel was highly reliable with a high Q30 quality score, on-target ratio, and coverage. The panel was time- and cost-efficient and enabled the detection of more mutations than whole-exome sequencing for the same patient. Pathogenic mutations in both PTCH1 and PTCH2 were detected in five of the 12 patients with Gorlin syndrome who were diagnosed based on clinical symptoms. Using this panel, the same mutation was identified in the patients and their blood relatives. In summary, this panel facilitated the highly reliable genetic diagnosis of Gorlin syndrome at a low cost, using only blood samples.